Influence Of Technostructural Interventions On Organizational Performance: A Case Study Of Commercial Banks In Kenya - Siruri Marwa, Moses; Namusonge , Dr. Mary J.; M. Kilika , Dr. James (International Journal of Scientific Research and Management (IJSRM), 2019)
Technostructural interventions are an expensive typology of organisation development interventions. Commercial banks in Kenya have however been seen to increasingly adopt these interventions in a bid to drive up performance. The literature, on the other hand, indicates that empirical studies on the effects of these interventions have indicated varied results across different sectors and settings. This study therefore sought to establish the effect of technostructural interventions on the performance of commercial banks in Kenya. The typologies of technostructural interventions considered were job enrichment, employee involvement and physical layout. The study adopted a cross sectional research design. Multivariate analysis indicated that job enrichment and physical layout do not have an effect on performance of commercial banks in Kenya. Employee involvement was however found to have a positive and significant effect on the perfomance of commercial banks in Kenya.